Mutagenesis by O6 meG residues within codon 12 of the human Ha-ras proto-oncogene in monkey cells. - Pletsa, V (1992)
The first or/and the second guanines of the human Ha-ras codon 12 (normally GGC) were substituted by O6 meG residues and the modified sequence was subsequently introduced into an SV40-based shuttle vector able to replicate in both simian cells and bacteria. After replication in simian COS7 cells (proficient in O6-alkyl-guanine transferase), plasmid DNA was extracted and mutations were screened in E. coli DH5 alpha cells. The vast majority of the mutations induced by O6 meG were G----A transitions. The mutation frequency observed at the second guanine of codon 12 (12G2 position: 3.75% +/- 0.4) was higher than the one observed at the first guanine (12G1 position: 1.09% +/- 0.6). This difference was confirmed by the results obtained when two adjacent O6 meG residues were positioned within codon 12. The higher mutation frequency observed for the 12G2 position could be attributed to differential repair or/and variation in polymerase fidelity. These results are in agreement with animal experiments where alkylating agents gave rise to mutation on G2 position of codon 12.